Testicular peritubular cells secrete a protein under androgen control that modulates Sertoli cell functions. - Skinner, M K (1985)
Peritubular cells of the seminiferous tubule synthesize component(s) that stimulate Sertoli cells in culture to increase the production of androgen-binding protein and testicular transferrin. The active peritubular cell component(s) are trypsin-sensitive, heat-sensitive, acid-stable molecule(s) having a molecular weight between 50,000 and 100,000. These specific factors(s) are referred to as P Mod-S to designate protein(s), produced by peritubular cells (P), that modulate the functions of Sertoli cells (S). The degree of stimulation by P Mod-S is comparable to that obtained by maximal hormonal stimulation of the synthesis of ABP and transferrin by Sertoli cells. Levels of P Mod-S secreted into the medium by primary cultures of peritubular cells are increased in the presence of testosterone. Comparable concentrations of 17 beta-estradiol do not stimulate peritubular cells to synthesize P Mod-S. Data are interpreted to indicate that androgens act on testicular peritubular cells to increase the formation of P Mod-S and that P Mod-S may modulate the properties of adjacent Sertoli cells. Findings are discussed in relation to the nature of mesenchymal-epithelial cell interactions in the seminiferous tubule and to the possible role of P Mod-S as a mediator of androgen actions of Sertoli cells.